OC-077 Does Faecal Occult Blood Testing Help Identify Ileo-Colonic Neuroendocrine Tumours in the UK Bowel Cancer Screening Programme (BCSP)?. (17th August 2016) - Basuroy, R; O'Donnell, K; Brooks, C; Srirajaskanthan, R; Ramage, J
Abstract : Introduction: There has been an increase in the incidence of ileo-colonic NETs in recent years, partly from endoscopy. There is no published data on the incidence of NETs diagnosed in the UK 'double' screen BCSP of initial Faecal Occult Blood stool test (FOBt) and, if abnormal, colonoscopy. The incidence (per 100 k) of colorectal cancer (CRC) in FOBt abnormal UK BCSP colonoscopy is 55 times that of the population incidence (10 k vs 184). 1 The aim of this study was to identify NETs diagnosed and recorded at UK BCSP colonoscopy between 2005–14. Methods: Data requests were made to UK BCSP for details of screened populations, abnormal FOBts, and colonoscopies performed and CRCs diagnosed. NET related queries were run across 3 database tables; 'Polyp Histology Polyp Architecture', 'Lesion Type', 'Histology Snomed'. Incidence (per 100 k) was compared with those from the SEER database; 2 small intestine and colorectal NETs 2.4; rectal 0.9, other colonic 0.4, appendiceal 0.2, small intestine 0.9. Results: 13 million people completed FOBt screening with 260 k abnormal FOBt and 217 k colonoscopies. 146 NETs were identified with an incidence of 67 (per 100 k colonoscopies). The incidence of NETs (per 100 k colonoscopies) by site was 29 rectal, 18 other colonic, 1 appendiceal, and 11 small intestine. Ratios of BCSP to SEER incidences was 29 overall NET, 32 rectal, 45 other colonic, 5 appendiceal, and 12 small intestine. Conclusion: The incidence of NETs at UK BCSP colonoscopy following an abnormal FOBt is markedly higher than the SEER population incidence. The effect is greatest for rectal and other colonic NETs although less than that seen with CRC (55 x) following FOBt screening. There is no published data on the incidence of small intestine NETs identified from terminal ileum intubation during 'single' or 'double screen' BCSP. However, the rectal NET incidence in the UK FOBt BCSP is lower (29 per 100 k colonoscopies) than that published from 'single screen' colonoscopy-only BCSP (50–70 per 100 k colonoscopies). 3 This suggests endoscopic screening itself is more helpful than FOBt screening in identifying rectal NETs. References: 1 Logan RF, Patnick J, Nickerson C, et al . Outcomes of the Bowel Cancer Screening Programme (BCSP) in England after the first 1 million tests. Gut 2012;61 (10):1439–1446. 2 Modlin IM, Lye KD, Kidd M. A 5-decade analysis of 13, 715 carcinoid tumours. Cancer 2003;97 (4):934–959. 3 Kaminski M, Polkowski M, Regula J. Prevalence and endoscopic features of rectal neuroendocrine tumours (carcinoids) among 50148 participants of the Polish colorectal-cancer screening programe. Gut 2007;56 (Suppl III): A310. Disclosure of Interest: None Declared